First-in-human clinical series of a novel conformable large-lattice pulsed field ablation catheter for pulmonary vein isolation - Reddy, Vivek Y; Anter, Elad; Peichl, Petr; Rackauskas, Gediminas; Petru, Jan; Funasako, Moritoshi; Koruth, Jacob S; Marinskis, Germanas; Turagam, Mohit; Aidietis, Audrius; Kautzner, Josef; Natale, Andrea; et al. (Europace, 2024)
AIMS: Pulsed field ablation (PFA) has significant advantages over conventional thermal ablation of atrial fibrillation (AF). This first-in-human, single-arm trial to treat paroxysmal AF (PAF) assessed the efficiency, safety, pulmonary vein isolation (PVI) durability and one-year clinical effectiveness of an 8 Fr, large-lattice, conformable single-shot PFA catheter together with a dedicated electroanatomical mapping system. METHODS AND RESULTS: After rendering the PV anatomy, the PFA catheter delivered monopolar, biphasic pulse trains (5-6 s per application; ∼4 applications per PV). Three waveforms were tested: PULSE1, PULSE2, and PULSE3. Follow-up included ECGs, Holters at 6 and 12 months, and symptomatic and scheduled transtelephonic monitoring. The primary and secondary efficacy endpoints were acute PVI and post-blanking atrial arrhythmia recurrence, respectively. Invasive remapping was conducted ∼75 days post-ablation. At three centres, PVI was performed by five operators in 85 patients using PULSE1 (n = 30), PULSE2 (n = 20), and PULSE3 (n = 35). Acute PVI was achieved in 100% of PVs using 3.9 ± 1.4 PFA applications per PV. Overall procedure, transpired ablation, PFA catheter dwell and fluoroscopy times were 56.5 ± 21.6, 10.0 ± 6.0, 19.1 ± 9.3, and 5.7 ± 3.9 min, respectively. No pre-defined primary safety events occurred. Upon remapping, PVI durability was 90% and 99% on a per-vein basis for the total and PULSE3 cohort, respectively. The Kaplan-Meier estimate of one-year freedom from atrial arrhythmias was 81.8% (95% CI 70.2-89.2%) for the total, and 100% (95% CI 80.6-100%) for the PULSE3 cohort. CONCLUSION: Pulmonary vein isolation (PVI) utilizing a conformable single-shot PFA catheter to treat PAF was efficient, safe, and effective, with durable lesions demonstrated upon remapping.
Keywords: Equipment Design; srdeční katétry; Recurrence; Female; Electrophysiologic Techniques, Cardiac; Atrial Fibrillation; elektrofyziologické techniky kardiologické; Pulmonary Veins; výsledek terapie; ženské pohlaví; Action Potentials; Catheter Ablation; Time Factors; časové faktory; lidé; recidiva; katetrizační ablace; Treatment Outcome; venae pulmonales; srdeční frekvence; Heart Rate; Male; Aged; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; Cardiac Catheters; design vybavení; Middle Aged; akční potenciály; Humans